Cultural plurality in ancient magical texts and practices: Graeco-Egyptian handbooks and related traditions - Bortolani, Ljuba Merlina; Furley, William D.; Nagel, Svenja; Quack, Joachim Friedrich (Orientalische Religionen in der Antike, 2019)
Der vorliegende Sammelband ist das Ergebnis einer Konferenz in Heidelberg im Jahr 2014. Die Beitragenden untersuchen die verschiedenen, facettenreichen Aspekte magischer Texte und Praktiken in der Antike mit besonderem Fokus auf griechisch-ägyptischen magischen Papyri. Der Schwerpunkt liegt auf Fragen der kulturellen Vielfalt und Verschmelzung; von früheren ägyptischen, mesopotamischen und griechischen magisch-religiösen Überlieferungen über die neuartigen Entwicklungen im griechisch-römischen Ägypten bis hin zu deren Einbindung in die jüdische und byzantinische Magie.InhaltsübersichtLjuba M. Bortolani/Svenja Nagel: Introduction & Acknowledgements Part I: Egyptian, Greek and Mesopotamian Traditions of Magic: Different Genres, Perception of the 'Other' and Possible Transcultural Exchange Franziska Naether: Magical Practices in Egyptian Literary Texts: in Quest of Cultural Plurality – William Furley: Magic and Mystery at Selinus. Another Look at the Getty Hexameters – Daniel Schwemer: Beyond Ereškigal? Mesopotamian Magic Traditions in the Papyri Graecae Magicae Part II: Cultural Plurality and Fusion in the Graeco-Egyptian Magical Papyri (PGM/PDM)Single Handbooks and Magical Techniques Richard Gordon: Compiling P. Lond I 121 = PGM VII in a Transcultural Context – Svenja Nagel: Illuminating Encounters: Reflections on Cultural Plurality in Lamp Divination Rituals – Ljuba M. Bortolani: 'We Are Such Stuff as Dream Oracles Are Made on': Greek and Egyptian Traditions and Divine Personas in the Dream Divination Spells of the Magical Papyri – Christopher A. Faraone: Cultural Plurality in Greek Magical Recipes for Oracular and Protective Statues Specific Spells and Deities Joachim Friedrich Quack: The Heliopolitan Ennead and Geb as a Scrofulous Boar in the PGM. Two Case Studies on Cultural Interaction in Late-Antique Magic – Richard Phillips: Traditions of Transformation and Shape-Shifting in PGM XIII 270–77 – Adria Haluszka: Crowns of Hermanubis: Semiotic Fusion and Spells for Better Business in the Magical Papyri – Marcela Ristorto: Love Spell and Hymn to Aphrodite in PGM IV (2891–941) Part III: Integration and Transformation of Graeco-Egyptian Magic in Jewish and Byzantine Spells Gideon Bohak/Alessia Bellusci: The Greek Prayer to Helios in Sefer Ha-Razim, in Light of New Textual Evidence – Michael Zellmann-Rohrer: Incantations in Byzantine and Post-Byzantine Greek: Change and Continuity.